FAKTOR FAKTOR YANG MEMPENGARUHI UKURAN FUNGSI AUDIT INTERNAL PADA PERUSAHAAN DI INDONESIA (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2012) - Yolanda Pratami; Hardi -; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of the diffusion of ownership, management share ownership, leverage, company size, reporting levels, and organisational complexity toward size of internal audit function on the companies